2018
DOI: 10.1002/med.21550
|View full text |Cite
|
Sign up to set email alerts
|

Orexin supplementation in narcolepsy treatment: A review

Abstract: Narcolepsy is a rare, chronic neurological disease characterized by excessive daytime sleepiness, cataplexy, vivid hallucinations, and sleep paralysis. Narcolepsy occurs in approximately 1 of 3000 people, affecting mainly adolescents aged 15 to 30 years.Recently, people with narcolepsy were shown to exhibit extensive orexin/hypocretin neuronal loss. The orexin system regulates sleep/wake control via complex interactions with monoaminergic, cholinergic and GABA-ergic neuronal systems.Currently, no cure for narc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 80 publications
0
19
0
Order By: Relevance
“…The number of orexin neurons is selectively reduced in human narcolepsy, and canine narcolepsy is caused by a mutation of the OX2R gene [33,34]. Intranasal administration of orexin peptide, orexin neuron transplants, and orexin gene therapy are promising approaches to the treatment of narcolepsy [35,36]. The selective OX2R agonist YNT-185 has been shown to ameliorate cataplexylike episodes in a mouse model of narcolepsy [37].…”
Section: Sleep Disorders Especially Primary Insomniamentioning
confidence: 99%
“…The number of orexin neurons is selectively reduced in human narcolepsy, and canine narcolepsy is caused by a mutation of the OX2R gene [33,34]. Intranasal administration of orexin peptide, orexin neuron transplants, and orexin gene therapy are promising approaches to the treatment of narcolepsy [35,36]. The selective OX2R agonist YNT-185 has been shown to ameliorate cataplexylike episodes in a mouse model of narcolepsy [37].…”
Section: Sleep Disorders Especially Primary Insomniamentioning
confidence: 99%
“…Orexin A (hypocretin-1) employs a postsynaptic excitatory action on prefrontal cortex neurons by inhibiting potassium currents via the activation of protein kinase C (PKC) and phospholipase C (PLC) signaling pathways (Xia et al, 2005 ). Orexin deficiency is related to narcolepsy according to the reviews (Mahoney et al, 2019 ; Nepovimova et al, 2019 ; Mignot et al, 2021 ). Therefore, high Ih current due to the lack of orexin can play a role in the pathogenesis of narcolepsy.…”
Section: Resultsmentioning
confidence: 99%
“…Various modalities have been proposed, including orexin agonists, gene therapy, and cell transplantation. Recent experiments in mice showed that central administration of orexin in orexin-cell-ablated mice improved wakefulness and reduced cataplexy 77. Other studies showed amelioration of narcolepsy symptoms with peripherally administered YNT-185 (non-peptide selective orexin type-2 receptor agonist)78 and TAK-925 (orexin 2 receptor selective agonist)79 in mice models, providing further proof of concept.…”
Section: Current Treatmentsmentioning
confidence: 93%